The Effects of Some Synthetic Compounds on In Vitro Fibrinolytic Activity Measured by Different Methods and the Relevance to Activity In Vivo - Baillie, A.J; Sim, A. K (Thrombosis and Haemostasis, 1972)
The activity of several synthetic compounds, rated from good to poor (or inactive) fibrinolytic activators, has been assessed by two different commonly-used in vitro methods. Compounds shown to be active over a narrow concentration range in the hanging clot test were shown to be inhibitors of plasmin and trypsin in the casein-olytic test. The inhibitory activity of these compounds was shown to increase with increasing substrate concentration and apparent activity in the hanging clot test. Possible explanations and relevance of these observations are discussed.